1982
DOI: 10.1080/00986448208911637
|View full text |Cite
|
Sign up to set email alerts
|

Water Simulation of Sodium Reactors

Abstract: The thermal hydraulic simulation of a large sodium reactor by a scaled water model is examined. The Richardson Number, friction coefficient and the Peclet Number can be closely matched with the water system at full power and the similarity is retained for buoyancy driven flows. The simulation of thermal-hydraulic conditions in a reactor vessel provided by a scaled water experiment is better than that by a scaled sodium test. The results from a correctly scaled water test can be tentatively extrapolated to a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Fiorina [10,11] studied this issue and used a ray-tracing code and a Gaussian beam summation method to perform wave propagation simulation and compared amplitude and time of flight fluctuations with known analytical results. Similarities between water and sodium have been well described [12] and it is thus possible to reproduce liquid sodium behavior with hot water experiments. Fiorina [10,11] represents the fluctuating medium by a homogeneous and isotropic turbulent medium: temperature spatial fluctuations are considered in the stochastic domain and modeled by a Fourier mode summation technique.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Fiorina [10,11] studied this issue and used a ray-tracing code and a Gaussian beam summation method to perform wave propagation simulation and compared amplitude and time of flight fluctuations with known analytical results. Similarities between water and sodium have been well described [12] and it is thus possible to reproduce liquid sodium behavior with hot water experiments. Fiorina [10,11] represents the fluctuating medium by a homogeneous and isotropic turbulent medium: temperature spatial fluctuations are considered in the stochastic domain and modeled by a Fourier mode summation technique.…”
Section: Introductionmentioning
confidence: 94%
“…Characteristic sizes of flow heterogeneities, typically ranging between 0.1 cm and 10.0 cm, are also large compared to the wavelengths of the ultrasonic waves considered [12].…”
Section: Numerical Simulations 41 Modeling Of the Propagation Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…By the non-dimensionalization of the appropriate equations one may derive the necessary conditions for exact similitude. Grewal & Gluekler ( 1982 ) have shown that in order that an experimental model represent an exact similitude of the LMFR pler,,a it is essential that:…”
Section: Problems Of Scaling Lmfrsmentioning
confidence: 99%
“…axi =k axiaxi _xi_]. ui j+ "_T(6) =mm In these equations the overbars represent averaged quantities and the index on the left superscript signifies the coordinate direction in which the summation convention does not apply. The left superscript "v" signifies volume-averaged quantities.This set of equations is no longer a closed set -due to the non-linearities in the governing equations _ -the averaging process gives rise to second order correlations that must be modeled,.…”
mentioning
confidence: 99%